ANALISA KAMPUH V TERHADAP PLAT ASTM A36 MENGGUNAKAN AWS E 7016, PADA ARUS 60, 80 DAN 100 A DENGAN METODE UJI TARIK DAN KEKERASAN - Meryanalinda M.T; Sochib M.T; Agus Suparman, S.T (Wahana Teknik, 2021)
In this study, the aim of this study was to test the welding of the weld seam v. with variations in current strength of 60, 80 and 100 Amperes. Welding machine using RYU 450 watts, electrodes using AWS E 7016 and plate material for specimens using ASTM A36 with data properties of elastic modulus of 200,000 Mpa, yield strength 250 Mpa, tensile strength 400 Mpa, and mass density 7850 kg/m3 data on material properties obtained from SolidWork 2018 data base. The approach method for making test specimens uses a jig paper tool that is used as a mall (pattern) and jig welding as a specimen plate holder or specimen plate handle (given welding studs) so that the specimen plate does not move when welding is seam and functions also to minimize the deformation caused by welding. This test was carried out at the Industrial Service Standardization and Policy Agency, the Industrial Research and Standardization Institute, which is located on Jalan Jagir-Surabaya, with the number of tests for each variation of 2 x tests. At a current of 60 amperes the tensile strength values ​​are 350.08 Mpa and 177.67 Mpa, 80 amperes produce a tensile strength value of 348.64 Mpa and 224.44 Mpa, 100 amperes produce a tensile strength value of 285.17 Mpa and 275.47 Mpa. The results of the fractures from the above tests all show in the weld section. The hardness test of specimens-01.02 and 03 produced values ​​on the weld surface of 88.6, HRB, 88.9 HRB and 88.7 HRB, on the HAZ surface of 71.3 HRB, 75.2 HRB and 76.9 HRB